2004
DOI: 10.1016/j.eurpsy.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character inventory (TCI) personality profile in metamphetamine abusers: a controlled study

Abstract: We applied the temperament and character inventory (TCI) personality questionnaire in 41 inpatients dependent on metamphetamine, and 35 controls. Novelty seeking, harm avoidance and self-transcendence were significantly higher, and persistence, self-directedness and cooperativeness were significantly lower in the patients than in the healthy volunteers. The detected differences may be important for prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 12 publications
7
22
4
2
Order By: Relevance
“…Lower levels of persistence also are associated with a diagnosis of metamphetamine abuse (Hosak et al, 2004), but studies using the TCI found no association between alcohol abuse and persistence, in spite of findings of higher novelty seeking and lower self-directedness in alcoholic patients compared to healthy individuals (Basiaux et al, 2001;Le Bon et al, 2004). Persistence is related to the ability to persevere despite frustration and fatigue, and it is possible that bipolar patients with low persistence may have more difficulty in stopping alcohol use despite its adverse consequences.…”
Section: Personality Differences In Bipolar Disorder With Comorbid Almentioning
confidence: 99%
“…Lower levels of persistence also are associated with a diagnosis of metamphetamine abuse (Hosak et al, 2004), but studies using the TCI found no association between alcohol abuse and persistence, in spite of findings of higher novelty seeking and lower self-directedness in alcoholic patients compared to healthy individuals (Basiaux et al, 2001;Le Bon et al, 2004). Persistence is related to the ability to persevere despite frustration and fatigue, and it is possible that bipolar patients with low persistence may have more difficulty in stopping alcohol use despite its adverse consequences.…”
Section: Personality Differences In Bipolar Disorder With Comorbid Almentioning
confidence: 99%
“…El hallazgo de altos niveles de ED ha sido observado previamente en pacientes con otras patologías como cefalea tensional crónica 17 , fibromialgia 18 , adicción a anfetaminas 19 , trastorno de ansiedad generalizado 20 , trastorno obsesivo-compulsivo 21 y síndrome de fatiga crónica 22 .…”
Section: N V E S T I G a C I ó Nunclassified
“…Novelty seeking is also higher in addicts than the general population (29)(30)(31) seekers are capricious, curious, impulsive, and chaotic individuals, who desperately look for new stimuli (18). The majority of these features, including high-risk behaviors, impulsivity, anti-social behaviors, substance use, and multiple sexual relations are also observed in the fast-life strategy (32).…”
Section: Discussionmentioning
confidence: 99%